PENERAPAN PENDEKATAN PROSES UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI DI SEKOLAH DASAR - Hasibuan, Risa Rizalia; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the improvement of narrative writing skills with the approach of the process of class V students of Muhammadiyah Primary 3 Pontianak City. This research uses descriptive method with form of action research class (PTK) and is collaborative. This research was conducted for three cycles with each cycle one time meeting. The results of the study design study (RPP) of the cycle I average score 3.85, cycle II average score 3.94, and cycle III average score 3.98. The results of research implementation of the learning cycle I score average of 2.68, cycle II average score 3.96 and cycle III average score 3.98. The result of the research write narrative essay from cycle I mean value 61,62, second cycles II value 73,62 and cycle III with average value 79,96. Total mastery reach 90% or 18 people with 75 increase from cycle I which only 15%. From the data obtained can be concluded that the application of process approach can improve the writing skills of student narrative. Thus, research using a process approach to learning writing writing can involve students more active, enthusiastic and more effective. Keywords: Process Approach, Improve, Writing Narrative Essay